(untitled) (Medicine Today, 2014)
The single fetal death in multiple pregnancy is not rare. Death of one fetus in multiple pregnancy increases the risk of mortality and morbidity of the surviving fetus. Proper diagnosis and intervention in appropriate time can improve the maternal and neonatal outcome. Adequate counselling psychological support and close follow up are mandatory. DOI: http://dx.doi.org/10.3329/medtoday.v26i1.21320 Medicine Today 2014 Vol.26(1): 69-70